Colimacoris joceliae, sp. nov. (Hemiptera: Miridae: Deraeocorinae: Hyaliodini): A new species from Panama, with a Key to the species of Colimacoris - Kim, Junggon; Roca-Cusachs, Marcos; Rider, David A.; Jung, Sunghoon (Zootaxa, 2021)
The new Neotropical hyaliodine Colimacoris joceliae Kim & Jung, sp. nov., is described from Panama. Morphological information, including a description and diagnosis of the new species is presented with photographs. A key for the identification of the species of Colimacoris is also provided.